2002
DOI: 10.1046/j.1365-2133.2002.04698.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining lesional short-contact dithranol therapy of psoriasis with a potent topical corticosteroid

Abstract: Intermittent addition of clobetasol-17-propionate ointment enhanced the antipsoriatic efficacy of short-contact, high-dose dithranol therapy in terms of clearing capacity and treatment duration, without shortening remission duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Swinkles et al (EG B) performed a study on the efficacy of monotherapy with 5 ϫ/weekly clobetasol applied to three plaques per patient versus 1 ϫ/daily dithranol or 5 ϫ/weekly combination use of dithranol and clobetasol [104]. Each monotherapy resulted in complete remission in 80 % of plaques, while combination therapy achieved full remission in 100 %.…”
Section: Dithranol and Topical Steroidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Swinkles et al (EG B) performed a study on the efficacy of monotherapy with 5 ϫ/weekly clobetasol applied to three plaques per patient versus 1 ϫ/daily dithranol or 5 ϫ/weekly combination use of dithranol and clobetasol [104]. Each monotherapy resulted in complete remission in 80 % of plaques, while combination therapy achieved full remission in 100 %.…”
Section: Dithranol and Topical Steroidsmentioning
confidence: 99%
“…For dithranol monotherapy, there was one grade A 2 study [96], 11 grade B studies [97][98][99][100][101][102][103][104][105][106][107], and 1 grade C study [108]. For dithranol monotherapy, there was one grade A 2 study [96], 11 grade B studies [97][98][99][100][101][102][103][104][105][106][107], and 1 grade C study [108].…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of dithranol in combination with an ultrapotent topical corticosteroid (clobetasol propionate) was studied during a treatment of 39 days using an intra-individual comparison between (1) dithranol short-contact treatment with daily applications of clobetasol-17-propionate ointment and (2) daily applications of clobetasol-17-propionate ointment only. Dithranol in combination with clobetasol-17-propionate showed a better and faster clearing response and the subsequent remission periods were more prolonged [12].…”
Section: Combinationsmentioning
confidence: 99%
“…Analysing several statistical parameters the authors concluded that intermittent addition of clobetasol-17-propionate ointment enhanced the antipsoriatic efficacy of short-contact, highdose dithranol therapy in terms of clearing capacity and treatment duration, without shortening remission duration. 66 A prospective, single-center, open-label, right/left comparison of 28 lesion pairs in 15 patients was conducted by Bowman et al They treated psoriasis patients for a 2-week period, followed by a 4-week post-treatment observation phase. Calcipotriene-and tazarotene-treated lesions showed nearly identical efficacy with their matched clobetasoltreated counterparts but erythema improved significantly more in clobetasol-treated lesions (P  0.05).…”
Section: 52mentioning
confidence: 99%